Jean Baudrillard : from hyperreality to disappearance : uncollected interviews - Smith, Richard G. (Lecturer in human geography); Clarke, David B., 1964- (Edinburgh University Press, 2015)
23 collected interviews with the renowned French philosopher and cultural commentator, Jean Baudrillard. This new collection gathers 23 highly insightful yet previously difficult-to-find interviews with Baudrillard, ranging over topics as diverse as art, war, technology, globalisation, terrorism and the fate of humanity. From familiar themes to the less well understood aspects of his thought, these interviews give you an overview of Baudrillard's ideas - without the jargon typical of written texts. Read as Baudrillard himself discusses, explains and elaborates on his ideas, making this collection essential for understanding many of his other works. Key Features. The first book of collected interviews with Baudrillard for over two decades Valuable to new and seasoned readers of Baudrillard and to students and academics in philosophy, sociology, literary theory, art history, architecture, film and photography, cultural studies, human geography and media studies Gathers many unknown and otherwise unavailable pieces into one volume